A Third Latin Translation of Ibn al-Ṣaffār’s Treatise on the Uses of the Astrolabe - Nothaft, C. Philipp E. (Mediterranea, International Journal on the Transfer of Knowledge, 2023)
This article addresses the contents of the twelfth-century fascicle contained in MS Lyon, Palais des Arts, 45, which is largely devoted to texts on computus and the astrolabe. Included among the latter are 24 anonymous chapters on astrolabe use, which appear to stem from a previously unrecorded translation of Ibn al-Ṣaffār’s Kitāb fī-l-ʿamal bi-l-asṭurlāb (Book on the Uses of the Astrolabe). This would make the chapters in the Lyon manuscript the third such translation to come to light after the well-known twelfth-century translations by John of Seville and Plato of Tivoli. The article includes an edition of the text in question as well as two further appendices providing a breakdown of its content as well as a description of the Lyon fascicle.